Video-assisted Overtaking System enabled by V2V Communications - Pedro António Ribeiro Magalhães (2020)
V2X (Vehicle-to-Everything) is a promising technology to diminish road hazards and increase driving safety. This thesis focuses in the transmission of video between vehicles (V2V, Vehicle-to-Vehicle) in an overtaking situation, helping drivers to be more aware and less error-prone in these situations. In the implementation, the vehicle reads from vehicle's CAN and GPS data to setup the system, streams his Line of Sight to the overtaking vehicle and uses DSRC as the communication technology.